2015
DOI: 10.1107/s1600577515009686
|View full text |Cite
|
Sign up to set email alerts
|

Resonant inelastic X-ray scattering spectrometer with 25 meV resolution at the CuK-edge

Abstract: An unparalleled resolution is reported with an inelastic X-ray scattering instrument at the Cu K-edge. Based on a segmented concave analyzer, featuring single-crystal quartz (SiO 2 ) pixels, the spectrometer delivers a resolution near 25 meV (FWHM) at 8981 eV. Besides the quartz analyzer, the performance of the spectrometer relies on a four-bounce Si(553) high-resolution monochromator and focusing Kirkpatrick-Baez optics. The measured resolution agrees with the ray-tracing simulation of an ideal spectrometer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
(28 reference statements)
1
17
0
Order By: Relevance
“…We aim, for future mounting, to glue the diced quartz surface onto an Si wafer, dice the opposite quartz thin layer again and then glue, by sandwiching the Si wafer and the diced quartz, into the tempered glass substrate. This procedure is similar to that described by Ketenoglu et al (2015).…”
Section: Fabricationmentioning
confidence: 98%
See 1 more Smart Citation
“…We aim, for future mounting, to glue the diced quartz surface onto an Si wafer, dice the opposite quartz thin layer again and then glue, by sandwiching the Si wafer and the diced quartz, into the tempered glass substrate. This procedure is similar to that described by Ketenoglu et al (2015).…”
Section: Fabricationmentioning
confidence: 98%
“…In fact, sapphire has been used for making IXS spherical analyzers (Yavaş et al, 2007;Sergueev et al, 2011). Quartz and LiNbO 3 spherical analyzers have also been proposed for IXS studies, since they offer high energy resolution at lower photon energies (Sutter et al, 2005(Sutter et al, , 2006Gog et al, 2013;Hö nnicke et al, 2013;Ketenoglu et al, 2015). One of the main motivations for the development of quartz-based spherical analyzers is that they offer a large choice of reflections within a given photon energy interval owing to the lower crystal symmetry with respect to silicon or germanium.…”
Section: Introductionmentioning
confidence: 99%
“…These reflections give about 420 different back-reflection energies that are almost continuously distributed in the medium energy range 5-16 keV. This indicates that one can use quartz to make nearback-reflection ( ' 90 ) analyzers (or monochromators) for any photon energy E > 5 keV (Ketenoglu et al, 2015;Honnicke et al, 2016;Sutter & Yavaş, 2017). It also means that one can make quartz polarizers ( ' 45 ) for arbitrary energies.…”
Section: Introductionmentioning
confidence: 99%
“…3) was oriented and cut by a dicing saw with a metal-bonded diamond blade into a slab with dimensions of 33 Â 38 Â 3 mm from a grade A -SiO 2 singlecrystal block (TEW Japan). Grade B (Sutter et al, 2005) and grade A (Sutter et al, 2006;Hö nnicke et al, 2013;Ketenoglu et al, 2015;Huang et al, 2018, Macrander et al, 2019 -SiO 2 single crystals (TEW Japan) have been previously characterized and it was found that the relative variations in the lattice parameters (Ád/d) are smaller than 1 Â 10 À7 for the grade A research papers DuMond diagrams (DuMond, 1937) used to estimate the divergence and bandwidth obtained with the Si 220 MBBM. (a) DuMond diagram overview for the InSb 111 DCM and the MBBM showing the region of exact XBD where the energy resolution (Á/) appears infinitely small.…”
Section: Setting Up the A-sio 2 1120 Analyser Crystalmentioning
confidence: 99%
“…Our goal is to determine whether the energy resolution under such extreme conditions can be further improved in comparison with that for the exact XBD condition. For this purpose, the XBD h-beam is characterized by using a grade A high-quality -SiO 2 1120 single crystal (TEW, Japan) (Sutter et al, 2006;Hö nnicke et al, 2013Hö nnicke et al, , 2016Ketenoglu et al, 2015;Yavaş et al, 2017;Gog et al, 2018;Kim et al, 2018;Huang et al, 2018;Said et al, 2018, Macrander et al, 2019 as the analyser at energies around 3.2 keV.…”
Section: Introductionmentioning
confidence: 99%